STEM teachers’ beliefs about the relevance and use of evidence-based information in practice: a case study using thematic analysis - Hillmayr, Delia; Reinhold, Frank; Holzberger, Doris; Reiss, Kristina (Frontiers in Education, 2024)
The term evidence-based practice has gained importance in teacher education as well as in everyday school life. Calls from policymakers, academics, and society have become increasingly apparent, that teachers' professional actions should not exclusively be based on subjective experiential knowledge but also empirical evidence from research studies. However, the use of evidence comes along with several challenges for teachers such as often lacking applicability of available sources or limited time resources. This case study explores how teachers (n = 12) at secondary schools think about the relevance and usage of evidence-based information in practice as well as the barriers associated with it. As we see a particular need for evidence-based teaching in STEM disciplines, we focus on these subjects. A thematic analysis of the data indicates that the teachers generally rate relevance highly, for instance, seeing opportunities for support and guidance. However, the actual use of evidence-based information in the classroom is rather low. The teachers most frequently mentioned the feasibility of implementation in class as a quality indicator of evidence-based information. Based on the data, we discuss possible conclusions to promote evidence-based practice at schools. Furthermore, the study opens up directions for further research studies with representative teacher samples in various disciplines.